Novel Insights into Gonadotropin-Releasing Hormone Action in the Pituitary Gonadotrope - Brown, Jessica L.; Roberson, Mark (Seminars in Reproductive Medicine, 2017)
The hypothalamic-pituitary-gonadal axis controls reproduction via a series of hormones regulating gonadal function through interconnected feedback loops. Secretion of hypothalamic-derived gonadotropin-releasing hormone (GnRH) integrates inputs from higher brain centers to coordinate the activity of the pituitary gonadotrope and the biosynthesis and secretion of the gonadotropins which ultimately regulate gonadal function. Failure of GnRH to serve as the central integrator of this system has been associated with hypogonadotropic-hypogonadism and clinical infertility, while pharmacological application of GnRH analogs and gonadotropins have important implications of the treatment of such infertility. Furthermore, the GnRH–GnRH receptor system has been characterized in several types of cancer and may offer therapeutic possibilities in their treatment. Given the central role of GnRH action in the control of fertility, it is of paramount importance to understand the molecular basis of control of GnRH action in the pituitary gonadotrope, including new and novel alternate ways to modulate GnRH action and gonadotropin secretion. The goal of this review is to discuss several new findings in this field focusing on novel regulators of GnRH action.
Keywords: GnRH; gonadotropin; pituitary; signaling